(untitled) (Revista Educação, Artes e Inclusão, 2023)
The purpose of this article is a clipping of a master’s dissertation defended in 2019 and proposes to build a bibliographic review that inserts the games for educational context. Games are grat instruments on the teaching-learning process and on this article, by qualitative configuration, we tried to present the different aspects of games, from the ways they take on playfulness, the games definition and their histories, games on education and mre about the differences among games, toys and games. Divided into six parts, this article emphasizes the contribution of games to the environment from different perspectives, angles and perspectives.The results, presents on the theoretical framework of this study, indicate that games, if used in a planned and guided way, in addition to having a favorable environment for its operationalization can constitute important and significant tools on the teaching-learning process. If the games are well planned And directed can help teachers on the teaching learning process.